Chemical Fingerprinting and Multi-marker Determination of the Roots of Indigofera stachyoides by UHPLC-Q-TOF/MS - Yang, Ya-Xin; Wang, Ai-Min; Wang, Zheng; Wang, Yong-Lin; Zhang, Jin; Liu, Jun-Hong; He, Xun; Li, Yong-Jun; Hao, Xiao-Yan; Liao, Shang-Gao (Current Pharmaceutical Analysis, 2015)
An ultra-high performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (UHPLC-Q-TOF/MS)-based chemical fingerprinting and three-markers (protocatechuic acid, catechin, and epicatechin) determination method has been developed for the quality control of the roots of Indigofera stachyoides. The optimal chromatographic condition was achieved on a Synergi Hydro-RP (2.00 mmx100 mm, 2.5 μm) column with linear gradient elution using water containing 0.1% formic acid and acetonitrile containing 0.1% formic acid as the mobile phase. The flow rate was 0.3 mL/min, the injection volume was 3 μL, and the column temperature was set at 35°C. The method is based on a full-scan negative electrospray ionization mass spectrometry (ESI-MS) at m/z 50 1000, with the capillary voltage of 2800 V, nebulizing gas (N2) pressure of 1.2 Bar, drying gas (N2) flow rate of 8.0 L/min and gas temperature of 200°C. MS quantification was based on the high resolution extracted ion chromatogram of the target ion with deviation set at ± 0.005. Satisfactory repeatability, stability and precision were observed for the chemical fingerprint. For quantification, excellent linear behavior over the investigated concentration range was observed with regression coefficient (R2) > 0.9976 for all analytes. The RSDs of intra-day and inter-day precision are less than 1.7%. Recoveries were in the range of 98.4 104.8%. Quantitative analysis results showed that contents of the three common compounds differed significantly among different batches of the roots of I. stachyoides from different growing areas in Guizhou Province. The method was reliable, accurate, and repeatable, and can be applied to the routine quality assessment of I. stachyoides.
Keywords: multi-marker determination